Efektivitas kombinasi tablet tambah darah dengan suplementasi vitamin C terhadap peningkatan hemoglobin pada mahasiswi - Mahmudah, Amaliah; Sulastri, Sulastri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: A common health problem in women is low hemoglobin levels, which can cause anemia. Someone who experiences anemia can affect their daily activities, including female students who are taking part in the teaching and learning process on campus. Increasing hemoglobin levels can be overcome by routinely consuming iron tablets and to help the absorption of iron in the blood, it can be combined with consuming vitamin C supplements. Purpose: To determine the effect of the combination of iron tablets with vitamin C supplementation on increasing hemoglobin in female students. Method: Quantitative quasi-experimental research with a pre-test and post-test design with a control group. The population of this study were undergraduate students of Nursing, Faculty of Health Sciences, Muhammadiyah University of Surakarta with a sample size of 50 participants, divided into two groups, namely 25 intervention participants and 25 control participants. The intervention group consumed iron supplements combined with vitamin C supplementation for 28 days, each participant received 10 iron tablets accompanied by lemon, while the control group only consumed iron supplements. Results: The majority of menstrual periods in the intervention group were in the range of 6-7 days, while in the control group they were in the range of 6-9 days. Most menstrual cycles in the intervention and control groups were regular. The average difference between pre and post in the intervention group was 1.37 g/dl, while in the control group it was only 0.20 g/dl. In addition, the p value in the control group was 0.000 (≤ α 0.05), while in the control group it was 0.060. Conclusion: The intervention of providing iron supplement tablets combined with vitamin C supplements can have an effect on increasing hemoglobin levels, compared to only consuming iron supplement tablets. Keyword: Anemia; Hemoglobin; Iron Supplement Tablets; Vitamin C. Pendahuluan: Masalah kesehatan pada wanita yang sering terjadi adalah kadar hemoglobin yang rendah, sehingga menyebabkan anemia. Seseorang yang mengalami anemia dapat berpengaruh pada aktivitas kesehariannya, termasuk mahasiswi yang sedang mengikuti proses belajar mengajar di lingkungan kampus. Peningkatan kadar hemoglobin dapat diatasi dengan rutin mengonsumsi tablet tambah darah dan untuk membantu penyerapan zat gizi besi dalam darah dapat dikombinasikan dengan mengonsumsi suplementasi vitamin C. Tujuan: Untuk mengetahui pengaruh kombinasi tablet tambah darah dengan suplementasi vitamin C terhadap peningkatan hemoglobin pada mahasiswi. Metode: Penelitian kuantitatif quasi-eksperimen rancangan pretest dan posttest with control group. Populasi penelitian ini adalah mahasisiwi S1 Keperawatan FIK UMS dengan total sampel yang digunakan sebanyak 50 partisipan, dibagi menjadi dua kelompok, intervensi sebanyak 25 partisipan dan kontrol sebanyak 25 partisipan. Kelompok intervensi mengonsumsi tablet tambah darah yang dikombinasikan dengan suplementasi vitamin C selama 28 hari, setiap partisipan mendapatkan 10 tablet tambah darah disertai jeruk lemon, sedangkan kelompok kontrol hanya mengonsumsi tablet tambah darah saja. Hasil: Mayoritas lama menstruasi kelompok intervensi pada rentang 6-7 hari, sedangkan kelompok kontrol pada rentang 6-9 hari. Sebagian besar siklus menstruasi pada kelompok intervensi dan kontrol teratur. Selisih rata-rata pre dan post pada kelompok intervensi sebesar 1.37 g/dl, sedangkan pada kelompok kontrol hanya 0.20 g/dl. Selain itu, perolehan p-value kelompok kontrol sebesar 0.000 (≤ α 0.05), sedangkan kelompok kontrol sebesar 0.060. Simpulan: Intervensi tablet tambah darah yang dikombinasikan dengan suplemen vitamin C dapat memengaruhi peningkatan kadar hemoglobin, daripada hanya mengonsumsi tablet tambah darah saja. Kata Kunci: Anemia; Hemoglobin; Tablet Tambah Darah; Vitamin C.